Analisis Penyerapan Tenaga Kerja Lokal Lulusan P2TIM dan Implikasinya terhadap Kesejahteraan Masyarakat di Kabupaten Teluk Bintuni - Dudung, Daniel; Herpina, Herpina; Abdul Jalil, Sartika; Nor Islamy, Sulaiha (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study analyzes the employment absorption of graduates of the Oil and Gas Industry Education and Training Program (P2TIM) based on employment status, vocational field, training batch, work location, and employing company or institution. A descriptive quantitative design with a census approach was applied to 1,892 alumni recorded in the alumni tracer database. The data were analyzed using frequency distributions, percentages, current employment rate, previous employment absorption rate, labor market participation rate, and local placement proportion. The results show that 1,165 alumni (61.58%) were currently employed, 1,219 alumni (64.43%) had been employed, and 1,267 alumni (66.97%) had participated in the labor market. Among the 1,003 employed alumni whose work locations could be identified, 460 individuals (45.86%) worked in Teluk Bintuni/Tangguh. Welding recorded the highest employment rate (79.82%), while Scaffolding contributed the largest number of employed graduates (308 individuals). Employment rates across training batches ranged from 16.47% to 83.33%; however, these comparisons were affected by differences in the length of exposure to the labor market. The findings confirm P2TIM’s contribution to improving alumni access to employment but do not establish a causal effect on welfare because the database does not include indicators of income, consumption, pre-program conditions, or a comparison group.